PENGEMBANGAN MEDIA JUMPING NUMBER TREE BERBASIS SMART BOX MATERI POLA BILANGAN PADA PESERTA DIDIK KELAS I SD MUHAMMADIYAH 2 SURABAYA - Diva Adesya; Kunti Dian Ayu Afiani; Lilik Binti Mirnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objectives this study are 1) To determine validity Jumping Number Tree media based on smart box number pattern material for grade I SD 2) To determine the practicality of Jumping Number Tree media smart box number pattern material for grade I SD 3) This research uses development method Research and Developmen (R&D) the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The research conducted at SD Muhammadiyah 2 Surabaya. The subjects in this study are first grade students with as many as 29 students. The research was conducted from December 2023 to May 2024. The data collection techniques used questionnaires and tests, research instruments in the form of media and material expert validation sheets, teacher and learner response questionnaires, and test sheets. The results showed that the smart box-based Jumping Number Tree media very valid criteria with a percentage level 93% for media and material validation, practical as seen from the 96% teacher and 98% learner questionnaire responses, and effective as seen from results student learning completeness which got a percentage of 93%. It can be concluded smart box based Jumping Number Tree is valid, effective and practices for learning number patterns in grade I SD.